Pengembangan Website E-Canteen untuk Meningkatkan Pendapatan UMKM di Lingkungan Universitas Negeri Jakarta - Wildiansah, Muftiana; Safira; Sahara, Siti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Universitas Negeri Jakarta (UNJ) hosts numerous Micro, Small, and Medium Enterprises (MSMEs) that offer food and beverages. However, these MSMEs face challenges in reaching a broader customer base due to insufficient marketing efforts. This research aims to develop an E-Canteen website to enhance their income. The E-Canteen website serves as an online platform enabling MSMEs to sell their products to UNJ students, lecturers, and employees. The development of the E-Canteen website employs the System Development Life Cycle (SDLC) methodology with a Prototyping approach. The findings of this study indicate that the E-Canteen website significantly aids MSMEs within the Jakarta State University environment in increasing their revenue. By leveraging digital technology, the website facilitates more efficient customer interactions, ultimately boosting MSME visibility and sales